Pengaruh Kepemimpinan, Karakteristik Individu, dan Budaya Organisasi terhadap Kinerja Pegawai Dinas Kebudayaan & Pariwisata, dan Kepuasan Konsumen Industri Pariwisata di Jawa Timur - H. Eddy Yunus (Jurnal Aplikasi Manajemen, 2010)
This research aims to testify and analyzing the influences of leadership toward employee performance, leadership toward consumer satisfaction, leadership toward organization cultural, individual characteristic toward employee performance, individual characteristic toward consumer satisfaction, organization cultural toward consumer satisfaction, employee performance toward consumer satisfaction. This research designed by using Structural Equation Modeling Analysis. The analysis unit are civil employee performance in Cultural and Tourism Agency on 7 (seven) governments of second regencies in East Java province and its tourism industry consumers, all at once as respondent in this research. The result of Structural Equation Modeling testing: H1, H2, H3, H4, H5, H6, H7 and H8, its influences be larger. Satisfy consumer of tourism industry can be done with improving the employee performance of Cultural & Tourism Agency of East Java Province, through human resource development, with increasing people tourism awareness.For the middle and higher level leaders, in running duty shall be more get priority to pay attention in horizontal work system and improving their leadership effectiveness, developing their capabilities, to creating work climate which supporting and motivating their subordinates. For people of East Java is necessary to improving tourism awareness, either public people, Employees of Cultural & Tourism Agency, and inter Agencies in Province Governmental; and it can be seen from findings of researchers in East Java, Yogyakarta, and Bali.Keywords: Leadership, individual characteristic, organization culture, employee performance, consumer satisfaction.